Pengaruh Pajak, Exchange Rate, Profitabilitas, dan Leverage Pada Keputusan Melakukan Transfer Pricing - Cahyadi, Anisa Sheirina; Noviari, Naniek (E-Jurnal Akuntansi; Vol 24 No 2 (2018)DO - 10.24843/EJA.2018.v24.i02.p23, 2018)
The phenomenon of transfer pricing may occur due to management motivation to avoid tax, especially transfer wealth (earnings) between related parties. The aim of this study is to determine the effect of tax, exchange rate, profitability, and leverage manufacturing companies on the decision to transfer pricing. The research was conducted at a manufacturing company registered in Indonesia Stock Exchange (IDX), with purposive sampling method. The samples obtained are 15 companies with observation period for 3 years so that the number of samples is 45. Data obtained by downloading annual report of manufacturing companies listed on the Stock Exchange in 2014 - 2016. Analytical techniques used are logistic regression. The results of this study indicate that tax, profitability, and leverage have a positive influence on the company's decision to transfer pricing. While the exchange rate variable does not affect the company's decision to transfer pricing. Keywords : transfer pricing, taxes, exchange rate, profitability, leverage